超臨界二氧化碳環境下添加不同鈣矽比摻料對套管水泥力學、物理與化學性質之研究 - 林唐筠; Lin, Tang-Yun (2017)
二氧化碳捕獲與封存是目前公認最有效的減碳技術之一，台灣西部濱海深部鹽水層具有百億噸以上龐大的封存潛能。但封存場址處於高溫、高壓且潮濕環境下，注入的二氧化碳會與水反應形成碳酸，影響隔離套管與井孔岩壁的套管水泥(API-G 水泥)並產生碳酸化反應，使得水泥材料的力學性質降低，進而造成二氧化碳洩漏，縮短有效封存的時間。 因此本研究針對上述情形規劃對套管水泥(API-G 水泥)及添加不同配比之氧化鈣與二氧化矽之套管水泥進行試驗。 試驗規劃分成水泥漿體及水泥塊體，水泥塊體置入模擬井底高溫高壓環境(45°C、25MPa之超臨界二氧化碳溶於去離子水)，觀察經過不同反應時間(未反應、7、14、28、56、84 天)之物理、化學及微觀性質變化。研究結果發現在API-G水泥中添加5wt.%SiO2，會使鈣矽比明顯降低，矽原子分布較均勻，而微觀結構產生許多白色微小的矽晶體，此晶體能堆積填補孔隙使其結構更加緻密，增強水泥強度並降低透性，有較佳之防止水泥碳化而弱化之能力。 Carbon capture and storage (CCS) is regarded as one of the most effective carbon reduction technologies Deep saline aquifers in the coast of western Taiwan have the potential for storing more than 10 billion tons of CO2 However the storage site is exposed to high temperatures and pressures Consequently Injection of CO2 which reacts with water to form carbonic acid results in the carbonation of the insulating casings as well as casing cement (API Class G) on the borehole This reduces the mechanical properties of the cement material thereby causing CO2 leakage and shortening storage time Therefore this study proposes to carry a series of tests to the casing cement (API-G cement) and the additions of different proportions of calcium oxide and silica to casing cement (under a supercritical carbon dioxide dissolved in deionized water environment of 45C and 25 MPa) The changes of physical chemical and microscopic properties were observed after different reaction time (unreacted 7 14 28 56 84 days) The results show that the addition of 5wt % SiO2 in API-G cement will make a significant reduction in the ratio of calcite to silicon and a relatively uniform distribution of silicon atoms Many tiny white silicon crystals produced in microstructures can fill the pores to make the structure denser and enhance the strength of cement and reduce the permeability preventing the cement carbonization in a better way